The Improving students' mathematics learning outcomes through problem-based learning - Rara Priananda; Kartini; Maimunah; Zahratul Banat (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
The low level of students' mathematics learning outcomes served as the primary motivation for this study. This research aimed to improve the mathematics learning outcomes of ninth-grade students at Babussalam Junior High School, Pekanbaru, through the implementation of the Problem-Based Learning (PBL) model. The study employed a Classroom Action Research design consisting of two cycles, each comprising the stages of planning, action, observation, and reflection. The participants were 24 students from class IX.3 during the even semester of the 2024/2025 academic year. Data were collected using mathematics achievement tests administered at the end of each cycle. Data analysis focused on comparing students' learning outcomes across the pre-cycle, Cycle I, and Cycle II. The results indicate a significant improvement in students' mathematics learning outcomes following the implementation of the PBL model. The percentage of students achieving the expected level of learning mastery increased from 25% in the pre-cycle to 45.83% in Cycle I, and further rose to 91.66% in Cycle II. These findings demonstrate that the Problem-Based Learning model is effective in improving students' mathematics learning outcomes. Therefore, the application of PBL can be considered a viable instructional approach for enhancing mathematics achievement at the junior secondary level.